Vedligeholdelsespoetik og patriarkalske fortælleformer: Litterære strategier til synliggørelse af husarbejde i 1970’erne hos Marianne Larsen og Ursula K. Le Guin - Hauschildt, Mille Breyen (Passage - Tidsskrift for litteratur og kritik, 2025)
“Maintenance Poetics and Patriarchal Narrative Forms: Literary Strategies for Making Housework Visible in the 1970s in Marianne Larsen and Ursula K. Le Guin” The article examines the narration of housework in the 1970s through an analysis of two literary works from the period. It argues that these works employ classical heroic and patriarchal narrative forms as literary analogies for housework.Further, the article demonstrates that this seemingly non-feminist literary strategy reveals how certain feminized experiences such as maintenance work resist representation within established literary conventions, in the 1970s as well as today.